Resonance Light-Scattering Method for the Determination of Probenecid Based on a Complex with Aniline Blue - Sun, Qian; Ma, Jing; Wang, Maoqing; Mu, Jingnan; Du, Xiaoyan (Asian Journal of Chemistry, 2010)
The interaction of probenecid and aniline blue was characterized by resonance light-scattering (RLS) measurement. Thereby, a new method for the determination of probenecid with high sensitivity and selectivity by using resonance light-scattering technique was developed. At pH 0.6-1.2, probenecid reacted with aniline blue to form an ion-association complex which resulted in considerable enhancement of resonance light-scattering intensity and a new spectrum appeared. The maximum scattering peaks of the resonance light-scattering spectrum were at 430 and 463 nm. Under optimal conditions, a linear relationship was obtained between the intensity of resonance light-scattering (IRLS) and the concentration of probenecid ranging from 4.0 × 10-7-3.2 × 10-5 mol L-1 with a detection limit of 4.9 × 10-8 mol L-1. Three synthetic positive urine samples were determined with satisfactory results and the recoveries were in the range of 92.2-106 %.